Public Investment in and for Agriculture: What Has it Achieved, and What Determines it? - Mogues, Tewodaj (2013)
US Launch of The State of Food & Agriculture 2012 at IFPRI "Investing in Agriculture for a Better Future". Presentation by Tewodaj Mogues, IFPRI.